2012
DOI: 10.1007/s10995-012-1085-9
|View full text |Cite
|
Sign up to set email alerts
|

Infant Mortality and the Risk of Small Size for Gestational Age in the Subsequent Pregnancy: A Retrospective Cohort Study

Abstract: To examine the association between prior infant mortality and subsequent risk for small for gestational age (SGA). This population-based, retrospective cohort study used the Missouri maternally linked, longitudinal dataset (1989–2005). Analyses were restricted to women who had two singleton pregnancies during the study period. Logistic regression was conducted to obtain adjusted odds ratios (AOR) and 95 % confidence intervals (CI) for the association between infant mortality in the first pregnancy and SGA in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
2
4
0
1
Order By: Relevance
“…Among the neonatal related factors, small size neonates were at higher risk of death than those average size neonates were. This finding was similar with previous studies conducted in Kenya, Ethiopia, Nigeria, and Indonesia [21, 2628]. This might be small size neonates were highly susceptible for different infections due to having low immunity defense.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the neonatal related factors, small size neonates were at higher risk of death than those average size neonates were. This finding was similar with previous studies conducted in Kenya, Ethiopia, Nigeria, and Indonesia [21, 2628]. This might be small size neonates were highly susceptible for different infections due to having low immunity defense.…”
Section: Discussionsupporting
confidence: 92%
“…Socio demographic and economic factors [10–20], maternal biological and obstetric factors such us: early age 1st pregnancy [1720], delivery and pregnancy complications [18, 2124], antenatal care (ANC) visit [18, 19, 21, 24], parity [21, 23], and birth space < 24 months [18, 24, 25] were reported having statistical significant association with NM. In line with this, neonatal factors, like size at birth [21, 2628], gestational age (GA) < 37 weeks [11, 13, 26, 27], delivery and health system related factors [16, 18, 21, 30–34], and behavioral and psychosocial factors [35, 36] were also shown statistically significantly associated with risk of NM.…”
Section: Introductionmentioning
confidence: 73%
“…The separate and combined effects of key pregnancy complications ( Salihu et al, 2013 ), identified from maternal hospital records were tested. These complications included hospitalisation during pregnancy for infections, anaemia, diabetes, hypertension, preeclampsia, eclampsia, abruptio placentae, placenta previa, other placental disorders, premature rupture of membranes and renal disorders (see Supplementary Table 1 for relevant ICD-codes).…”
Section: Methodsmentioning
confidence: 99%
“…The second grouping includes baseline pregnancy risk factors, such as multiple gestation, birth spacing < 18 months, maternal age, and parity, which are largely unmodifiable from the commencement of pregnancy [ 18 ]. The third grouping includes key pregnancy complications that might be a precursor of infant mortality, such as nutritional deficiencies, placental disorders, prematurity, and infection [ 19 ]. The last group includes other maternal factors and exposures which are known risk factors for infant mortality or may indicate maternal vulnerability or household dysfunction, such as substance use or mental health related service contacts, external causes of injury, and having other children in contact with the child protection system.…”
Section: Methodsmentioning
confidence: 99%
“…The separate and combined effects of key pregnancy complications identified from maternal hospital records were evaluated. Pregnancy complications included the effects of infection-related hospitalisations, anaemia, diabetes, hypertension, preeclampsia, eclampsia, abruptio placentae, placenta previa, other placental disorders, premature rupture of membranes and renal disorders during pregnancy on infant mortality (Additional file 1 ) [ 19 ]. Complications were excluded due to low incidence or non-significance ( p > 0.05), including hospitalisations for anaemia, diabetes, hypertension, preeclampsia, and eclampsia (Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%